Chemical and Physical Characteristics of Edible Films, Based on κ- and ι-Carrageenans with the Addition of Lapacho Tea Extract - Jancikova, Simona; Dordevic, Dani; Jamroz, Ewelina; Behalova, Hana; Tremlova, Bohuslava (Foods (Basel, Switzerland), 2020)
The aim of the study was to characterize antioxidant and textural property differences of edible films prepared with the addition of lapacho extract (LE). The experimentally produced edible films also contained different carrageenans (ι- and κ-carrageenan). The κ- and ι-carrageenan, glycerol and the different addition of LE (5%, 10%, 20%) were used as ingredients for forming films. The pH and viscosity were measured for film forming solutions (before drying). The following analyses were performed on films: the total polyphenol content (TPC), Ferric Reducing Antioxidant Power (FRAP) and 2-Diphenyl-1-Picrylhydrazyl (DPPH). Optical parameters were analyzed by the determination of UV-Vis spectra. The structure of films was characterized by scanning electron microscopy. The gained results indicated that the use of different gelling agents (ι- and κ-carrageenan) resulted in statistically significant (p < 0.05) differences in textural properties (strength and breaking strain) of produced edible films. The highest antioxidant properties and TPC had a κ film with 20% LE (DPPH: 87.63 ± 0.03%; TPC: 233.75 ± 0.104 mg gallic acid/g). According to these results, it can be concluded that edible films with the highest concentrations of added lapacho extract can serve as a good source of antioxidant compounds. Certainly, these properties can be usefully incorporated into the wrapped food commodity.
Keywords: kappa carrageenan; lapacho; iota carrageenan; antioxidant properties; textural properties